FORECASTING HEALTH INDICATORS OF PAKISTAN - Majid, Abdul; Aslam, Muhammad; Kashif, Muhammad; Altaf, Saima (Journal of Ayub Medical College Abbottabad, 2016)
Background: Forecasting of health indicators is of great importance for health policy makers. This study is aimed to forecast some important health indicators like crude death rate (CDR), crude birth rate (CBR), and infant mortality rate (IMR) and total fertility rate (TFR) of Pakistan. Methods: In this retrolective study, annual data of these indicators for years 1984-2010 have been used. The simple linear regression model with time as independent variable has been used to forecast these health indicators. Results: The within-sample forecast results are close enough to the actual values. All the forecast values of the stated indicators tend to decrease with time. The forecast values of CDR, CBR, IMR and TFR for year 2020 are 12.85, 5.61, 43.61 and 0.93, respectively. Conclusion: Although the forecast values show an improvement in health indicators of Pakistan but the IMR is expected to remain high even in 2020, a concern for the health policy makers. Keywords: Crude birth rate; Crude death rate; Health indicator; Infant mortality rate; Time trend model; Total fertility rate